Screening and characterization of 10398a polymorphism in invasive breast cancer in Malay population of peninsular Malaysia - Zafarina, Zainuddin (Pusat Pengajian Sains Kesihatan, 2013)
The rnitochd~drial DNA (mtDNA) 10398 polymorphism is hypothesised to alter a mitochondrial subunit of the electron transfer chain and is associated with several neurodegenerative disorders and cancers. Methods: In this study, an mtDNApolymorphism at nucleotide position 10398 was screened in 101 Malay female patients with invasive breast cancer and 90 age-matched healthy female controls using minisequencing analysis. Results: The Malay women with the 10398G variant showed a significantly increased risk of invasive breast cancer (OR = 2.29, 95% CI 1.25-4.20, P = 0.007). lnmlunohistochemistry analysis was conducted to investigate the effect of this polymorphism on the levels of apoptosis in breast cancer cells. The level ofBax (a pro-apoptotic protein) expression was significantly higher than that of Bcl-2 (an anti-apoptotic protein) in patients carrying the G allele (P = 0.016) but not in those carrying the A allele (P = 0.48). Conclusion: Based on these findings, we propose that the mtDNA 10398 polymorphism may be a potential risk marker for breast cancer susceptibility in the Malay population.